Comparison between the standardized absorbent paper points test and the Schirmer’s tear test to evaluate tear production in clinically healthy dogs - Huaringa P, Víctor (2015)
The aim of the study was to determine normal values of tear production in crossbred dogs using the standardized absorbent paper points test (SAPPT) in comparison with the Schirmer’s tear test (STT). A total of 33 dogs (66 eyes) of dolichocephalic skull type, between 2 to 6 years of age and of medium size (15-24 kg) were used. The mean tear production value by SAPPT was 20.85 ± 1.44 mm/min (range: 18-24) and by STT was 18.05 ± 1.58 mm/min. A positive weak correlation was found between SAPPT and STT values.